Pengaruh Promosi Online Terhadap Keputusan Pembelian Mahasiswa Pengguna Shopee di Universitas Tidar - Raffi Aprian Syaputra; Sri Setyaningrum; Laura Qurrotul Aini; Nadhira Mutiara Ramadhani; Syifana Dewinta; Joko Tri Nugraha (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The growth of e-commerce in Indonesia has prompted platforms such as Shopee to optimize their online promotional strategies to attract consumers and boost purchasing decisions. This study aims to analyze the influence of online promotions on consumer purchasing decisions on the Shopee application among students at Tidar University. A quantitative approach was employed through survey technique. Data were collected from 110 active students from the Law, Public Administration, and Communication Studies programs at Tidar University selected using purposive sampling. Primary data were obtained via questionnaire distributed online through Google Form, and secondary data from scientific journals and books. The research instrument consisted of 14 statement items measured on a 5-point Likert scale and was found to be valid and reliable with Cronbach's Alpha of 0.925 for the online promotion variable and 0.873 for the purchasing decision variable. Data were analyzed using descriptive statistics, Pearson's correlation test, and simple linear regression via IBM SPSS Statistics). The results revealed a regression equation of Y = 4.096 + 0.732X with a significance level of 0.001, proving that online promotion has a positive and significant effect on purchasing decisions, with a coefficient of determination (R² = 0.553) indicating that online promotions account for 55.3% of the variation in consumer purchasing decisions. These findings imply that Shopee and similar e-commerce platforms should consistently optimize varied promotional strategies including discounts, free shipping, flash sales, and vouchers to enhance consumer purchasing decisions, particularly among the Gen-Z demographic.